Evaluation of structural systems in slender high-rise buildings. Issue 2 (3rd April 2018) - Walsh, Patrick; Saleh, Ali; Far, Harry
Abstract: With the rapid population growth and scarcity of developable space, especially in large cities, there is a need for increased density in both commercial and residential housing, and hence a strong demand to maximise floor space by constructing not only tall, but also slender buildings. This study considers different structural systems available for constructing slender high-rise buildings and evaluates their feasibility in terms of the lateral deformation being one of the key governing design criteria for very tall buildings. To examine the performance of different structural systems in buildings of varying height and floor plan, this study applies finite element analyses in a parametric study to compare nine different building configurations under static loading with heights varying from 80 to 460 m. The study shows that buildings with square footprints can achieve greater heights over rectangular footprints with the same area and that multiple towers when connected structurally at one or more levels can achieve even greater heights.